Meningkatkan Hasil Belajar Pak dengan Metode PBL Berbantuan E-LKPD - Hotris Siregar (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
Education is a systematic process that aims to develop the potential, knowledge, skills, attitudes, and character of individuals, so that they can become individuals who are useful in their personal, social, and work lives. The main goal of education is to prepare individuals to face life's challenges, contribute to society, and achieve complete self-development. Education plays an important role in shaping civilization and encouraging the progress of a nation. The quality of learning in schools is largely determined by two main factors, namely student learning motivation and teacher teaching creativity. However, at SDN 091448 Saribujawa, Catholic Religious Education learning often faces obstacles, such as the use of monotonous teaching methods, which have an impact on low student interest and learning outcomes. This study aims to improve student activity and learning outcomes through the application of the Problem-Based Learning Model (PBL) in grade V students of SDN 091448 Saribujawa, with a focus on how PBL can improve learning outcomes and students' self-understanding as developing individuals. The implementation of PBL supported by technology in the learning process has succeeded in increasing student motivation and their learning outcomes, as indicated by the increase in the average value from cycle I to cycle II. In addition, there was a significant improvement in student attitude indicators, such as cooperation, responsibility, and independence.